ACADEMIC ETHICS IN MODERN INDONESIA: Shaykh Hasan Ma’sum’s Thought on Students’ Ethics in His Tazkîr al-Murîdîn Sulûk Tharîqah al-Muhtadîn - Maisyaroh, Maisyaroh; Dahlan, Zaini; Al Farabi, Mohammad (State Islamic University North Sumatra, 2023)
Abstract: This article examines Shaykh Hasan Ma’sum’s thoughts on students’ ethics. The study represents the first research conducted on the ulama’s thoughts within the field of academic ethics. Employing a historical-biographical approach, this study adopts Kuntowijoyo’s historical writing model. Utilizing Shaykh Hasan Ma’sum’s works on students’ ethics as primary sources, the data is then analyzed using the interpretation method. The study reveals that this ulama’s perspective on students’ ethics is outlined in his book titled Tazkîr al-Murîdîn Sulûk Tharîqah al-Muhtadîn, which encompasses four distinct types of ethics: students’ ethics toward his teachers, friends, themselves, and his God (Allah SWT). He also added a chapter on the students’ ethics during dhikr. Furthermore, the study highlights the influence of the Naqshabandiah order, to which Shaykh Hasan Ma’sum belonged, as well as the thoughts of prominent Sufis such as Imam al-Ghazâlî, al-Suhrawardî, al-Qusyairî, Ibn ‘Arabî, and Abû Thâlib al-Makkî on his thought. Thus, Shaykh Hasan Ma’sum’s thoughts complement the existing scholarship on academic ethics in Islam.Keywords: academic ethics, students’, sufi order, Nusantara manuscripts, East Sumatra